Evaluation of the New Generation PAUD Kit for Early Childhood Teacher Education: First-Year Findings from a Multiyear Study - Esti Kurniawati Mahardika; Muktia Pramitasari; Erna Risnawati (Universitas Islam Negeri Palopo, 2026)
Educational Play Materials (APEs) are essential in supporting practice-based learning and preparing prospective early childhood teachers with the pedagogical competencies required for effective classroom practice. Although numerous studies have evaluated individual instructional media, limited empirical evidence is available regarding the formative evaluation of integrated educational kits designed for pre-service teachers, particularly within open and distance learning environments. This study aimed to conduct a formative evaluation of the New Generation Early Childhood Education (PAUD) Kit developed by the Early Childhood Teacher Education Program (PGPAUD), Universitas Terbuka, during the first year of a multiyear research project. A mixed-methods formative evaluation design was employed to examine the kit's practicality, usefulness, relevance, implementation, and distribution as a basis for product refinement. Data were collected through online questionnaires, tutorial observations, focus group discussions, and workshops involving 2,877 students, 87 tutors, and 17 Learning Material Coordinators across Indonesia. The findings revealed that the PAUD Kit effectively supported practice-based learning, particularly in the Cognitive Development Methods and Children's Play and Games courses. Among students who received the kit, 93% reported understanding its intended use; however, the overall utilization of the kit remained inconsistent due to unequal distribution and varying levels of tutor encouragement. Tutors considered the PAUD Kit relevant, practical, and safe for instructional use while recommending improvements in user guidelines, curriculum alignment, and instructional content. The study concludes that the New Generation PAUD Kit demonstrates considerable potential to strengthen practice-based learning in early childhood teacher education. More importantly, this formative evaluation provides evidence-based feedback for refining the PAUD Kit and supporting its broader implementation in the subsequent stages of the multiyear development project.